2015
DOI: 10.1590/s0004-28032015000200011
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy Electrophysiological Screening in Children With Celiac Disease

Abstract: -Background -The involvement of the peripheral nervous system in children with celiac disease is particularly rare. Objective -The aim of this study was to assess the need for neurophysiological testing in celiac disease patients without neurological symptoms in order to detect early subclinical neuropathy and its possible correlations with clinical and demographic characteristics. Methods -Two hundred and twenty consecutive children with celiac disease were screened for neurological symptoms and signs, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…After removal of duplicates and screening of titles and abstracts screening, 45 were eligible for full-text review. A total of 16 studies met all eligibility criteria and were included in the systematic review (Figure 1, Table 3) [10,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. Nine studies on gluten ataxia [10,20,21,22,23,26,28,31,32] and 13 articles on gluten neuropathy were included [10,19,20,22,24,25,26,27,28,29,30,32,33].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removal of duplicates and screening of titles and abstracts screening, 45 were eligible for full-text review. A total of 16 studies met all eligibility criteria and were included in the systematic review (Figure 1, Table 3) [10,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. Nine studies on gluten ataxia [10,20,21,22,23,26,28,31,32] and 13 articles on gluten neuropathy were included [10,19,20,22,24,25,26,27,28,29,30,32,33].…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies included, 50% (eight out of 16) were full-text, prospective analyses that reported global prevalence or incidence rates of gluten neuropathy and gluten ataxia [19,20,21,22,23,24,28,29]. See Box 1 for the definitions of CD, gluten ataxia, and gluten neuropathy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations